2017
DOI: 10.2174/1871526517666170622075154
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Insights on Target Receptors of Amiodarone in Human and Acanthamoeba castellanii

Abstract: The existing bioinformatics tools, ligand binding attribute prediction, and model building offer a specific method to establish homology of proteins, discover drug targets, and facilitate the investigation of the evolution of several types of cardinal ion channels from unicellular eukaryotes to multicellular species as humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…As previously reported (Baig et al., 2017), we found that both ACA1_270170 and ACA1_092610 had remarkable amino acid sequence homologies with TPC1, human L‐type Cav and P/Q type Cav as evident on multiple sequence alignments of these amoebal proteins with the aforementioned human types of Cav's (Figures ). We explored the evolutionary origins of family Ion_Trans and its subtypes TPC ion channel for its distribution in species and found that this family, and its subtypes were present in species as remote as prokaryotes, fungi, and uncharacterized unicellular eukaryotes (Finn et al., ) (Figures , a).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…As previously reported (Baig et al., 2017), we found that both ACA1_270170 and ACA1_092610 had remarkable amino acid sequence homologies with TPC1, human L‐type Cav and P/Q type Cav as evident on multiple sequence alignments of these amoebal proteins with the aforementioned human types of Cav's (Figures ). We explored the evolutionary origins of family Ion_Trans and its subtypes TPC ion channel for its distribution in species and found that this family, and its subtypes were present in species as remote as prokaryotes, fungi, and uncharacterized unicellular eukaryotes (Finn et al., ) (Figures , a).…”
Section: Discussionsupporting
confidence: 83%
“…Although some recent studies have reported targets of drugs like amiodarone on Na‐K channels in Acanthamoeba (Baig, Rana et al, 2017) and loperamide on human Cav like ACA1_167020 (Baig et al, 2017); to the best of our knowledge, this is the first time that transcriptomics, metagenomics, bioinformatic computational tools, and ligand binding attributes with experimentations have evidenced for origins and placement of Acanthamoeba Cav like proteins in the specie tree and provide clue toward them being the targets of amlodipine in Acanthamoeba spp.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As seen in this study, the encysted amoeba shifts its metabolic preference from one nutrient to another when a particular pathway like the activity of glucoside is targeted ( Figures 5 and 6) channels and preventing the formation of Ca 2+ -Calmodulin complex via specific drugs like Loperamide, Amlodipine and Prochlorperazine, the encysted amoebae were not able to survive in the encysted state (Figure 7a-c). For Loperamide, which is an inhibitor of voltage-gated calcium channels (Cav) and calmodulin (CaM) (Laurence, Bruce, Björn, 2011) it has been recently shown that it has amoebicidal effects on Acanthamoeba trophozoites (Figure 5b) are achieved by targeting a human-like Cav called CavAc (Baig et al, 2017). The Ca 2+ ions channels are also the targets of Amlodipine that are known to target Cav1.1, Cav1.2 subtypes, and carbonic anhydrase that has proven to be amoebicidal for the encysted amoeba as well (Figure 7c).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, for the first time we investigated the role of ion transporters in sensory perception in the cyst stage of A. castellanii belonging to the T4 genotype. Based on the genome information, the presence of potassium ion transporters has been suggested [15]. However, their functional role in phenotypic switching is missing.…”
Section: Introductionmentioning
confidence: 99%